Fibrinogen does not relate to cardiovascular or muscle manifestations in COPD: cross-sectional data from the ERICA study. Issue 12 (4th April 2018) - Mohan, Divya; Forman, Julia R; Allinder, Matthew; McEniery, Carmel M; Bolton, Charlotte Emma; Cockcroft, John R; MacNee, William; Fuld, Jonathan; Marchong, Mellone; Gale, Nichola Sian; Fisk, Marie; Nagarajan, Sridevi; et al.
Abstract : Cardiovascular and skeletal muscle manifestations constitute important comorbidities in COPD, with systemic inflammation proposed as a common mechanistic link. Fibrinogen has prognostic role in COPD. We aimed to determine whether aortic stiffness and quadriceps weakness are linked in COPD, and whether they are associated with the systemic inflammatory mediator—fibrinogen. Aortic pulse wave velocity (aPWV), quadriceps maximal volitional contraction (QMVC) force and fibrinogen were measured in 729 patients with stable, Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages II–IV COPD. The cardiovascular and muscular manifestations exist independently (P=0.22, χ 2 ). Fibrinogen was not associated with aPWV or QMVC (P=0.628 and P=0.621, respectively), making inflammation, as measured by plasma fibrinogen, an unlikely common aetiological factor.